Contemporary Atrium Architecture: A Sustainable Approach to the Determination of Smoke Ventilation Criteria in the Event of a Fire - Maria Brzezińska; Dorota Brzezińska (Energies, 2022)
Atria within buildings present an environment which allows smoke to spread around a building in a fire situation. This could create dangerous conditions for the evacuation of people. Smoke control ventilation systems in atria work in the case of a fire, keeping evacuation routes available for people. They play a significant role in sustainable, holistic building fire strategies, and are most often designed following prescriptive requirements. However, contemporary, complex atria with additional architectural elements—such as transversal balconies—may not meet the standard approach, and require individual, performance-based research. This article proves a thesis that the atrium’s architecture can impact the effectiveness of smoke control systems, and suggests how to verify them based on CFD simulations. In the presented example, the authors suggest an improvement of people’s safety in a fire scenario by extending the preliminary smoke control system parameters, or by providing smoke curtains at additional levels of the atrium.